Penguatan Nilai Kejujuran melalui Pendidikan Antikorupsi di Sekolah - Alfurkan, Alfurkan; Marzuki, Marzuki (Universitas Negeri Malang, 2019)
This article aims to describe the form of anti-corruption education to strengthen the value of honesty in schools, factors that encourage and inhibit the implementation of anti-corruption education, as well as solutions to overcome obstacles in the implementation of anti-corruption education. The study uses a qualitative approach with a case study type. Data collection was carried out through interviews, observations, and documentation studies. Data analysis uses interactive analysis. Anti-corruption education is carried out in two ways i.e, the honesty canteen and the learning of Pancasila and Citizenship Education. Supporting factors that influence the honesty reinforcement are teacher modeling, increased worship activities, and participation in organizational activities. The inhibiting factor is that canteens often suffer losses due to lack of supervision and teacher assistance. The solution to overcome these obstacles is to increase cooperation between teachers, increase supervision, carry out regular assistance, and support from families and communities.